Method Fundraising in Upgrade Funds Zakat Through The Partnership Program at Dompet Dhuafa Center - Sembiring, Muhammad Rifaldi Syahputra; Zen, Muhamad; Amalia, Alvina (Munazzama: Journal of Islamic Management and Pilgrimage, 2025)
Effective and professional zakat management is one of the keys to the success of zakat institutions in improving the welfare of the community. Amidst competition between Islamic philanthropic institutions and the increasing needs of the community, the right fundraising strategy is very important to ensure the sustainability of empowerment programs. This study aims to determine the fundraising method applied by Dompet Dhuafa Pusat, and to determine the results of the application of this method in increasing zakat funds. This study uses a qualitative approach with a case study method. Data were collected through in-depth interviews, observations, and document analysis related to partnership programs run by Dompet Dhuafa Pusat. The results of this study indicate that the Dompet Dhuafa Pusat fundraising method has succeeded in increasing zakat funds significantly through several strategic approaches. In addition, the results of the application of this fundraising method have been proven to provide real benefits for mustahik and the wider community.